The current knowledge on ASXL1-mutated acute myeloid leukemia - Andrzejewska, Marta; Lubarska, Marta; Czerwik, Jakub; Kipka, Anna; Kowalczuk, Klaudia (Journal of Education, Health and Sport, 2022)
Acute myeloid leukemia is a malignant hematopoietic cancer, in the pathogenesis of which the central role is played by the mutations of genes controlling maturation and apoptosis of bone marrow progenitor cells. A mutation in the ASXL1 gene, whose protein product takes part in the regulation of gene expression, is of prognostic importance, being a negative prognostic and predictive factor. It is estimated that the ASXL1 gene mutation occurs in 14.4-19.1% of patients with AML and is more frequent in men over 60 years of age. Aberrations of chromosomes 8 and 11 often co-occur with ASXL1 gene mutation in AML and may provide additional prognostically relevant information. Treatment of patients with AML is tailored to the patient depending on the risk group, karyotype aberrations and coexisting mutations. Many patients are not eligible for allo-HSCT, although this method significantly improves the survival of AML patients with ASXL1 gene mutations. Gilteritinib may also be used to treat these patients, but the multitude of associated mutations forces to rely on chemotherapy based on non-specific cytotoxic drugs. This review summarizes the most crucial information concerning the pathogenesis, peculiarities, diagnosis and therapy of AML with coexisting ASXL1 mutation.